2015
DOI: 10.1128/aem.01037-15
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Sodium, Calcium, and Magnesium Ion Concentrations That Inhibit Geobacillus Biofilms Have No Effect on Anoxybacillus flavithermus Biofilms

Abstract: cThis study investigated the effects of varied sodium, calcium, and magnesium concentrations in specialty milk formulations on biofilm formation by Geobacillus spp. and Anoxybacillus flavithermus. The numbers of attached viable cells (log CFU per square centimeter) after 6 to 18 h of biofilm formation by three dairy-derived strains of Geobacillus and three dairy-derived strains of A. flavithermus were compared in two commercial milk formulations. Milk formulation B had relatively high sodium and low calcium an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…For example, Ca 2þ and Mg 2þ are both essential in the regulation of several steps of cell division (Hepler 1994;Webb 1949). Somerton et al (2015) showed that supplementation of a milk formula with as low as 2 mM CaCl 2 or 2 mM MgCl 2 increased the biofilm formation of three Geobacillus spp while 100 mM NaCl significantly decreased biofilm formation showing that high free Na þ ions and low Ca 2þ and Mg 2þ were collectively needed to reduce biofilm formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Ca 2þ and Mg 2þ are both essential in the regulation of several steps of cell division (Hepler 1994;Webb 1949). Somerton et al (2015) showed that supplementation of a milk formula with as low as 2 mM CaCl 2 or 2 mM MgCl 2 increased the biofilm formation of three Geobacillus spp while 100 mM NaCl significantly decreased biofilm formation showing that high free Na þ ions and low Ca 2þ and Mg 2þ were collectively needed to reduce biofilm formation.…”
Section: Introductionmentioning
confidence: 99%
“…Two mechanisms have been proposed to explain the effect of divalent cations on biofilm development (Somerton et al 2015). Under the Divalent Cation Bridging (DCB) mechanism the divalent cations bind negatively charged sections of the extracellular polymeric substances (EPS) helping to both stabilize and strengthen the biofilm aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…The biofilms were sampled and screened at three temperatures (55°C, 60°C, and 65°C) for different incubation times (up to 144 h) to determine the biofilm production responses on 316 L type stainless steel surfaces. The biofilms were sampled with 10% reconstituted dry whole milk (Sigma-Aldrich) which had been autoclaved at 121°C for 5 min before ( Somerton et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…Improved biofilm production by Geobacillus spp. in milk results in high concentrations of free Ca 2+ and Mg 2+ [ 35 ].…”
Section: Biofilm Development In Food Processing Environmentsmentioning
confidence: 99%